Endangered intergenerational language transmission: evidence from the indigenous Dusun society of Sabah, Malaysia - Dani, Noor Aina; Mohd Kiram, Norazlina; Mohd Arif, Mohd Ariffin; Ombi, Kamarlin; Suhailin, Md. Roslan; Sha'ri, Sharil Nizam; Paul, Daisy (Universiti Putra Malaysia Press, 2019)
This is an attempt to determine factors contributing to endangered intergenerational language transmission of mother tongue as a home language. A survey was conducted using four questionnaires to collect data from 120 students of the Dusun ethnic group living in a rural area in Sabah, Malaysia. At the time of the study, the respondents were around 15 years of age. They have learned the standard Dusun language in the primary school. A set of determining factors was used to evaluate the endangered indigenous language. Findings indicated that intergenerational language transmission of the mother tongue as a home language has been severely endangered. Majority of the students agreed that the trend in the existing Dusun language domain was highly limited. Meanwhile, utilisation of the endangered language in new domains and media was minimal. Some external factors such as social needs have triggered a widespread change than simple addition of new vocabulary items. In more specific, changes in the social needs have led to a change in linguistic vitality among the people of this indigenous community despite the implementation of preschool and post-school reinforcements by the responsible party in Sabah. Finally, three initiatives for language revitalisation are proposed. These include increasing the important status of this language in the society, systematic instruction in schools, and utilising the language for information and communication knowledge. The paper should be of interest to those in the areas of Malaysian languages and ethno-linguistics.